Transformational Leadership Influence, Intrinsic Motivation and Compensation for Employees Performance PT. ABC - Sari, Dian Mega; Krisnandi, Herry; Digdowiseiso, Kumba (Ridwan Institute, 2024)
This research investigates the multifaceted influences of transformational leadership, intrinsic motivation, and compensation on employee performance within the context of PT. A B C. Employing a quantitative approach, data was gathered from 125 respondents through the administration of structured questionnaires. The study utilized both descriptive and inferential analyses, incorporating techniques such as linear regression and modeling tests. The findings revealed a positive and significant impact on employee performance, as demonstrated by the regression equation: Employee Performance = 0.317 (Transformational Leadership) + 0.220 (Intrinsic Motivation) + 0.328 (Compensation). The overall model proved to be statistically significant (ANOVA p-value < 0.001). Notably, transformational leadership (p < 0.001) and intrinsic motivation (p = 0.005) exhibited substantial effects on performance, while compensation, although included in the model, did not show a statistically significant impact (p = 0.10000). Based on the results, recommendations are proposed to enhance organizational performance. These include fostering improved communication skills among leaders, addressing intrinsic motivation factors among employees, and reassessing compensation strategies for greater effectiveness. Implementing these recommendations is anticipated to contribute to overall performance enhancement and organizational success.